Upaya Mereduksi Kecemasan Akademik pada Siswa melalui Konseling Kelompok REBT - Nur Halima, St; Amirullah, Muhammad; Bakhtiar, Muhammad Ilham (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2024)
This article explores the need to provide a deeper understanding of the problem of academic anxiety experienced by students in High School of Gowa, as well as explaining how the Rational Emotive Behavior counseling service was implemented and influenced the reduction of academic anxiety at the school. Even though there is already provision of services related to anxiety, the level of anxiety experienced by students is still relatively high. This article describes the implementation of Rational Emotive Behavior counseling services at SMAN 10 Gowa, by explaining the methods, obstacles and results obtained. A quantitative approach with a quasi-experimental design method is used to explain service implementation. Data collection was carried out using an anxiety level scale and observation. The analysis shows the main focus is on reducing anxiety levels in Rational Emotive Behavior counseling services. The main challenges faced include the complexity of individual problems, low participation in group counseling, and limited resources. Comprehensive review and ongoing evaluation are essential to improving services in the future.